Sustaining Arts Programs in Public Education (Journal of School Administration Research and Development, 2016)
The purpose of this qualitative research case study was to investigate leadership and funding decisions that determine key factors responsible for sustaining arts programs in public schools. While the educational climate, financial constraints, and standardized testing continue to impact arts programs in public education, Eastland High School, the site of this case study, managed to sustain its visual and perform- ing arts program. The foundation of this research study was shaped around understanding the key factors that sustained the arts program at Eastland High School. A qualitative lens utilized three research questions that investigated arts programs at the school, leadership decisions that supported the arts program, and funding decisions made at the site. Data triangulation was used to identify several emerging themes relevant to the three research questions. The implications of this case study indicated collaborative leadership and resourceful funding decisions sustain viable arts programs in public schools.